“INDIGENOUS PLACE IS WHERE SHE WANTS!”: A STUDY WITH UNIVERSITY INDIGENOUS WOMEN.: um estudo com mulheres indígenas universitárias. - Molina, Karina (2023)
This article aims to problematize the presence of indigenous women in a federal university in southern Brazil. Through a narrative investigation, understood as the study of experience, we interviewed nine indigenous academics from different courses at IFES. We propose a discussion about the role that college education has played, as an ally in the struggle for the visibility of indigenous women, marginalized subjects from native village to academy. In addition to the possibility of equal opportunities, affirmative actions result in university qualification not only for the indigenous cause, but also for returning to the native villages. At the same time, being at the university implies indigenous students resist not only their reality in the native communities, but at the university as well.